Analysis The Role of Stakeholders in Development Waterfall Tourism Mandi Angin in Air Berau Village Subdistrict Pondok Suguh Regency Mukomuko - Sri Indarti; Rosidin Rosidin; Ju’im Thaap; Nurul Trisnawati (Penerbit Jurnal Indonesia, 2022)
Study this aims to be able know Role Stakeholders in Development Waterfall Tourism Bath Wind in Air Berau Village Subdistrict Cottage treat Regency Mukomuko. Method used in study is Method study qualitative as well as use descriptive data analysis. Technique data analysis is in the form of stages that have been passed and taken by a researcher To use could conclude meaning from the data findings that have been collected . in study this use theory role stakeholders in development and management tourist from Theory of the womb in Amaliyah Reski Etc as description in To do analysis in To do development tourist there is three role stakeholders namely 1). Government, 2) Private, 3) Community. Results Study could show in development waterfall tour bath the wind in the village of water berau already existence role and each stakeholders involved by direct and active in follow development tourism, with be marked already built track enter Street going to location travel, already existence instruction direction Street going to travel, already built door enter/gate tourism, place area parking vehicle, promotion travel, clothes community group lover nature , installed rope/ rope for down cliff to travel, mutual cooperation. and promotion from social media youtube and creation write in the form of a blog from party private..